Just-In Time Production System Using Fuzzy Logic Approach and A Simulation Application - Ozdemir, Yavuz; Alcan, Pelin; Basligil, Huseyin; Dokuz, Cagri (TRANS TECH PUBLICATIONS LTD, 2012)
While firms are operating in a global competitive environment, they are subjected to changes because of the increased competitiveness and developed technologies. Therefore, this transformation process forces to produce with just-in-time production and low cost products or services and leads to customer satisfaction. Until today, competitive conditions, efficiency, productivity and quality of production, forced the firms to put more emphasis on production systems. Therefore, the firms are more interested in scientific analysis, planning and controlling of their production systems. As a result, one of the newest approaches is Just in Time (JIT) production system which emerged after WWII in Japan and aims to decrease the inventory cost and maximize the quality. The philosophy of this approach is to produce the necessary amount of production, when and where needed at the required quality. But JIT production system is weak in unclear species. For this purpose, the general and necessary solution is using fuzzy logic. In this paper we discussed about the simulation of an assembly line with 3 steps; firstly using Kanban production method, secondly non-using Kanban production method, and lastly using Kanban production method with fuzzy times. And also the comparisons of these steps will also be studied in this paper.
Keywords: Just in time production system; kanban; fuzzy logic; simulation; JIT PRODUCTION; PERFORMANCE; Engineering; Materials Science